Potential Medicinal Plants Which Are Mentioned in "Erupalaiseddiyarvaiththyavilakkam" - Sathyaseelan, V.; Sivalathajini, V. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2015)
The Siddha medicine is a traditional system based on a combination of ancient medicinal practitioners, appears as part of Jaffna Tamil's culture. The objective of this study explained our ancient traditional physicians use the 'ErupalaiSedddiyar Vaiththiya Vilakkam' to prepare our siddha internal and external medicines used by our native Jaffna medicinal plants. It was an descriptive study.The data were collected from 'ErupalaiSedddiyar Vaiththiya Vilakkam' (1929). Data were converted and regulated statistically,study was carried out during March 2015-July 2015. The results revealed, A total of 586 Medicinal plants were recorded. These Medicinal plants classified as 76 families. Out of these plants significant percentage 23.54% (138) of the Medicinal plants mentioned in synonyms. 3.07% (18) poisonous plants were also used for drug preparations, 12 internal, 4 external medicine varieties & 18 simple remedies are mentioned. According the siddha pharmaco dynamics potency that medicinal plants ultimately produce therapeutic efficacy for the promotion and preservation of positive health and prevention as well as cure of disease, there are two types of Virya(Potency), Usna(Hot) 88.72% (519), Sita(Cold) 11.28% (67). Medicinal plants classified in the gustatory sense (Taste), Pulippu(Sour) 6.99% (41), Kaippu(Bitter) 35.66% (209), Karppu(Pungent) 17.57% (103), Enippu(Sweet) 13.82% (81), Thuvarppu(Astringent) 25.93% (152). Our indigenous doctors including graduates should know translate the quotation exactly, because all valuable preparation's most of the ingredients mentioned in Synonyms. Therefore study of 'ErupalaiSedddiyar Vaiththiya Vilakkam', indigenous knowledge of Medicinal plants and medicines goes to undertaken the documentation and further research arise up from these Medicinal plants.
Keywords: Medicinal plants; ErupalaiSedddiyar Vaiththiya Vilakkam; Synonyms